The Mediation Role of Workload on The Influence of Competency on Employees' Turnover Intention in Retail Store Employees in Bengkulu City - Agustian, Harri; Susena, Karona Cahya; Hardinata, Dodi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to determine the mediating role of workload on the influence of competency on turnover intention of retail store employees in Bengkulu City. The approach used in this study is quantitative with data collection techniques through questionnaires obtained directly from the original source (respondents) to 200 retail store employees in Bengkulu City. The research data was processed using the SmartPLS version 4.1 analysis tool. The results of the study indicate that the direct effect indicates that H1 is rejected, that work competency does not have a significant effect on turnover intention in store employees in Bengkulu City. Based on the results of the hypothesis test, it shows that H2 is accepted, that work competency has a positive and significant effect on workload in store employees in Bengkulu City. Based on the results of the hypothesis test, it shows that H3 is accepted, that workload has a positive and significant effect on turnover intention in store employees in Bengkulu City. The results of the indirect effect study show that H4 is accepted, that work competency indirectly has a positive and significant effect on turnover intention through workload as an intervening variable in store employees in Bengkulu City.